Literatur (kepustakaan) keislaman dalam konteks pesantren - Musrifah Musrifah (IQRA`: Jurnal Ilmu Perpustakaan dan Informasi (e-Journal), 2018)
Universally, Islamic literature existing in boarding schools is preserved and passed down from generation to generation directly related to the religious sciences as inherited to Islamic society by past priests in the past called "yellow books". The books cover very short text to text composed of bold volumes of Arabic Grammar, Tajwid, Logic, Fiqh and Ushul Fiqh, Aqidah, Tafsir of the Qur'an, Hadith and Hadith Science, Morals and Sufism, History of Life Prophet and a tribute to the Prophet. For the yellow book format, although the advancement of printing technology is currently evolving, the yellow book format, the prints are still the same as they used to be, that is, generally not bound or wrapped in leather covers and yellow paper. Because to maintain physical characteristics that generally contain symbolic meanings, which seem to be more classical. The yellow book composed by earlier scholars or Islamic literature has not changed in terms of its contents, since the author or scholar who has been inhabited and his wisdom is no doubt, the scholars are the heirs of the Prophet, and so on. In addition, the yellow book functioned also by the boarding school as a reference in addressing all life challenges, as well as an arena of innovation to face the modern world.Keywords: literature, islam, pesantren